2009
DOI: 10.1002/humu.20913
|View full text |Cite
|
Sign up to set email alerts
|

DMDexon 1 truncating point mutations: Amelioration of phenotype by alternative translation initiation in exon 6

Abstract: Mutations in the DMD gene result in two common phenotypes associated with progressive muscle weakness: the more severe Duchenne Muscular Dystrophy (DMD) and the milder Becker Muscular Dystrophy (BMD). We have previously identified a nonsense mutation (c.9G>A; p.Trp3X) within the first exon of the DMD gene, encoding the unique N-terminus of the 427 kDa muscle isoform of the dystrophin protein. Although this mutation would be expected to result in severe disease, the clinical phenotype is very mild BMD, with amb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
58
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 68 publications
(61 citation statements)
references
References 23 publications
2
58
1
Order By: Relevance
“…These include the genes for RAG1 (Santagata et al 2000), NBS1 (Maser et al 2001 (Puel et al 2006), IkBa (McDonald et al 2007), PHOX2B (Trochet et al 2009), DMD (Gurvich et al 2009), and FAC (Yamashita et al 1996). A notable exception is the expression of a DN25 isoform of TP63 expressed from an allele with a nonsense mutation at codon 11 that manifests dominant effects and is associated with a Rapp-Hodkin/ Hay-Wells like syndrome (Rinne et al 2008).…”
Section: Discussionmentioning
confidence: 44%
“…These include the genes for RAG1 (Santagata et al 2000), NBS1 (Maser et al 2001 (Puel et al 2006), IkBa (McDonald et al 2007), PHOX2B (Trochet et al 2009), DMD (Gurvich et al 2009), and FAC (Yamashita et al 1996). A notable exception is the expression of a DN25 isoform of TP63 expressed from an allele with a nonsense mutation at codon 11 that manifests dominant effects and is associated with a Rapp-Hodkin/ Hay-Wells like syndrome (Rinne et al 2008).…”
Section: Discussionmentioning
confidence: 44%
“…Based on the molecular weight of the truncated protein and the sequence of the KCNQ1 gene, we hypothesized that because of the mutation in the original translation initiation site, the protein synthesis might start from the second initiation site at position 583 in exon 2 of KCNQ1 gene, generating a truncated protein missing the initial 158 residues compared to the full length of KCNQ1 protein. The mechanism was first described in the inherited arrhythmia syndromes, although it has been observed in other diseases (18)(19)(20). Ozisik et al found that an alternate translation initiation site circumvented an aminoterminal DAX1 nonsense mutation leading to a mild form of X-linked adrenal hypoplasia congenital (18).…”
Section: Discussionsupporting
confidence: 42%
“…Similar observations have been made for mutations of DMD . Encoded in exon 1, the c.9G>A (p.Tyr3*) variant is expected to cause a severe Duchenne muscular dystrophy (DMD); however, the clinical presentation is that of the milder Becker muscular dystrophy [Gurvich et al, 2009]. Immunoblot analysis of dystrophin detected a protein of reduced size consistent with translational reinitiation within exon 6.…”
Section: Discussionmentioning
confidence: 99%